STUDI KOMPARASI PREDIKSI UMUR PELAYANAN ANTARA CAMPURAN SUPERPAVE DAN AC-WC MENGGUNAKAN PERMODELAN VISKOELASTIK DAN ELASTIK - Muhamad Abdul Hadi; Miftahul Fauziah (TEKNISIA, 2022)
The performance of a pavement depends on a load of passing vehicles; in anticipation of these problems, alternative solutions are needed. One solution is using a Superpave mixture as a type of pavement. Previous studies concluded that the Superpave mixture performed better in receiving or distributing vehicle loads and resistance to submersion conditions. However, to strengthen this opinion, exploring it from another point of view is necessary. One of them is the mechanistic-empirical analysis of the KENPAVE program, which is needed to determine the prediction of service life. In this study, the AC-WC mixture was used as a comparison. The analysis started by calculating the stiffness modulus value for both types of pavements, determining the alternative pavement design plans to be applied using Bina Marga 2017 method, and ending the mechanistic-empirical analysis process using two modeling forms, namely viscoelastic and elastic. As a result, the Superpave mixture has a relatively higher predictive value of service life compared to the AC-WC mixture. This result applies to both the viscoelastic and elastic models. Suggestions for using an alternative with Bina Marga 2017’s design chart 3-B on FFF7 criteria are given regarding maximizing the performance of the Superpave mixture in the field. The mechanistic-empirical analysis of the design alternative shows that the predicted service life is above the 20-year design age limit, which is 30.7 years in the viscoelastic model and 40.9 years in the elastic model before the prediction of the first damage.